1983
DOI: 10.1159/000110516
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from Cerebrovascular Disease

Abstract: Average annual cerebrovascular disease (CVD) mortality rates (age-adjusted to the 1950 US population) were calculated using data from 1967 through 1973 for 33 countries. Rates range from 35.8/100,000/year (Philippines) to 196.7/100,000/year (Japan). There is also considerable variation among the nations of Europe and North America. Comparing these results with similar information for the 1950s shows a marked decrease for CVD mortality in approximately two-thirds of the countries for which data are available. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…21 This phenomenon probably can be explained, to some degree, by the fact that people in the urban district are sufficiently well educat- ed to realize and avoid the risks of cerebrovascular disease, and have better medical care with resultant decrease in the fatality rate. For instance, it has been shown that there was a decline of cholesterol and triglyceride levels in residents of Taipei city from 1973 to 1977, but not in residents of San-Chih county, a rural area near Taipei city.…”
Section: L3mentioning
confidence: 99%
See 2 more Smart Citations
“…21 This phenomenon probably can be explained, to some degree, by the fact that people in the urban district are sufficiently well educat- ed to realize and avoid the risks of cerebrovascular disease, and have better medical care with resultant decrease in the fatality rate. For instance, it has been shown that there was a decline of cholesterol and triglyceride levels in residents of Taipei city from 1973 to 1977, but not in residents of San-Chih county, a rural area near Taipei city.…”
Section: L3mentioning
confidence: 99%
“…In a study of mortality rates from ischemic heart disease (THD) from 1968 through 1976 for 27 countries, 21 Epstein and Pisa concluded that there is a tendency towards a decline for countries whose initial IHD mortality rates were high and the reverse is true for those with initially low rates. Ko reported that the IHD mortality rate in Taiwan was on the increase from 1971 to 1980.…”
Section: L3mentioning
confidence: 99%
See 1 more Smart Citation
“…Although mortality from cerebrovascular disease has decreased during this century in many developed coun tries [1,2], stroke is still the third largest cause of death in Great Britain and the U nited States and places a heavy burden on the individual, the community and health ser vices. Figures from the Oxford Community Stroke Pro ject suggest that about 111,000 people in Great Britain had a first-ever stroke in 1988 (crude annual incidence rate 2/1,000) [3], and prevalence estimates suggest that between 3-4 times that many people in the comm unity suffer from the after-effects of a stroke [4][5][6].…”
Section: Introductionmentioning
confidence: 99%